2014
DOI: 10.1111/hepr.12438
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of and risk factors for bile duct stones after living donor liver transplantation: An analysis of 100 patients

Abstract: In the present study, right lobe graft and bile duct strictures are independent risk factors for BDS formation after LDLT. More careful observation and monitoring are required in the patients with high-risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This study indicated that bile leaks and bile stones comprise 82.4% of biliary complications following LT 11 . One study found that the incidence of bile duct stones following LDLT was 10%, while another reported an incidence range of 1.8%‐18% 12,13 …”
Section: Discussionmentioning
confidence: 92%
“…This study indicated that bile leaks and bile stones comprise 82.4% of biliary complications following LT 11 . One study found that the incidence of bile duct stones following LDLT was 10%, while another reported an incidence range of 1.8%‐18% 12,13 …”
Section: Discussionmentioning
confidence: 92%
“…The incidence of bile duct stones after LT is 10% 35 and more than half of these patients experience biliary strictures. An FCSEMS is placed with a balloon or basket after the removal of common bile duct stones, however, since intrahepatic stones are located proximally to the stricture, they are difficult to remove.…”
Section: Discussionmentioning
confidence: 99%